Owning development : creating policy norms in the IMF and the World Bank - Park, Susan, 1976-; Vetterlein, Antje (Cambridge ; New York : Cambridge University Press, 2010)
"As pillars of the post-1945 international economic system, the International Monetary Fund (IMF) and the World Bank are central to global economic policy debates. This book examines policy change at the IMF and the World Bank, providing a constructivist account of how and why they take up ideas and translate them into policy, creating what we call 'policy norms'. The authors compare processes of policy emergence and change and, using archival and interview data, analyse nine policy areas including gender, debt relief, and tax and pension reform. Each chapter traces the policy norm process in order to shed light on the main sources and mechanisms for norm change within international organisations. Owning Development details the strength of these policy norms which emerge, then either stabilise or decline. The book establishes valuable insights into the strength of current development policies propounded by international organisations and the possibility for change"--
Machine generated contents note: Part I. Introduction: 1. Owning development: creating policy norms in the IMF and the World Bank Susan Park and Antje Vetterlein; Part II. Norm Emergence: 2. Internal or external norm champions: the IMF and multilateral debt relief Bessma Momani; 3. From three to five: the World Bank's pension reform policy norm Veronika Wodsak and Martin Koch; 4. The strategic social construction of the World Bank's gender and development policy norm Catherine Weaver; Part III. Norm Stabilization: 5. Lacking ownership: the IMF and its engagement with social development as a policy norm Antje Vetterlein; 6. Stabilizing global monetary norms: the IMF and current account convertibility Andre; Broome; 7. Bitter pills to swallow: legitimacy gaps and social recognition of the IMF tax policy norm in East Asia Leonard Seabrooke; Part IV. Norm Subsiding: 8. The IMF and capital account liberalization: a case of failed norm institutionalization Ralf J. Leiteritz and Manuela Moschella; 9. The World Bank's global safeguard policy norm? Susan Park; 10. The new public management policy norm on the ground: a comparative analysis of the World Bank's experience in Chile and Argentina Martin Lardone; Part V. Conclusion: 11. Do policy norms reconstitute global development? Susan Park and Antje Vetterlein.
Includes bibliographical references and index.
nif 07/05/13
Loans
Keywords: Economic policy; Economic development; International Monetary Fund; World Bank